Impact of Ureteral Muscle Layer Damage on Ureteral Healing after Endoureterotomy: Experimental Animal Study - Muñoz Guillermo, Victoria; Fernández Aparicio, Tomás; Sánchez-Margallo, Francisco. M; Soria, Federico (International Journal of Innovative Research in Medical Science, 2023)
Background: Endoureterotomy is a procedure that depends on healing by secondary intention. Healing of the ureteral muscle layer can provoke re-stricture after endoureterotomy. The aim of this comparative study was to assess the impact of ureteral muscle layer damage on ureteral healing after four endourological techniques. Methods: A total of 96 female pigs underwent initial endoscopic, nephrosonographic, and contrast fluoroscopic assessment of the urinary tract. After baseline studies, a ureteral stricture was created. Three weeks later, the ureteral stricture was diagnosed and treated. Animals were randomly assigned to four groups (Group-I, Balloon dilatation endoureterotomy; Group-II, Cold endoureterotomy with scissors; Group-III, Monopolar hot electrocautery; Group-IV, Holmium laser retrograde endoureterotomy) in which a double-pigtail ureteral stent was placed for 3 weeks. Follow-up evaluations were performed at 3–6 weeks. The final follow-up was completed at 5 months and included the aforementioned diagnostic methods and pathological study. Results: In terms of therapeutic success, complete resolution was observed in 83% of cases. No evidence of vesicoureteral reflux nor urinary tract anomalies were observed. None of the endoureteromy procedures showed statistically significant differences in ureteral muscle layer remodeling. However, less ureteral muscle layer damage was significantly associated with higher success rates in ureteral treatment and healing. The presence of a positive uroculture was associated with more extensive ureteral muscle layer damage. Conclusions: The results of this comparative study in a porcine model indicated that ureteral muscle layer damage after endoureterotomy did not differ significantly between the different analyzed endourological techniques. The extent of ureteral muscle layer damage is a predictive factor of successful ureteral healing after endoureterotomy.